MICROBIAL SPECTRUM AND OUTCOMES OF ENDOPHTHALMITIS AFTER INTRAVITREAL INJECTION VERSUS PARS PLANA VITRECTOMY. Issue 2 (February 2016) - Garg, Sunir J.; Dollin, Michael; Storey, Philip; Pitcher, John D.; Fang-Yen, Natalie Hsiao; Vander, James; Hsu, Jason
Abstract : Purpose: To compare infectious organisms and visual outcomes of endophthalmitis after intravitreal injection (IVI) with endophthalmitis after pars plana vitrectomy (PPV). Methods: Retrospective, comparative, consecutive case series of patients diagnosed with presumed infectious endophthalmitis after IVI of an anti-vascular endothelial growth factor medication or PPV between January 1, 2009, and October 1, 2012, from one center. Main outcome measures were infectious organism and final visual acuity. Results: Forty-four cases of presumed infectious endophthalmitis (17 culture positive) occurred after IVI and 19 cases (9 culture positive) occurred after PPV. Of note, 56.3% of culture-positive IVI cases were due to bacteria associated with oral flora, primarily Streptococcus species, compared with none in the PPV group ( P = 0.01). There was a trend approaching significance for IVI patients to have lost ≥3 lines of visual acuity compared with PPV patients at final follow-up ( P = 0.07). Within the IVI group, patients were more likely to have lost ≥6 lines of visual acuity at final follow-up when endophthalmitis was due to an organism associated with oral flora ( P = 0.007). Conclusion: Endophthalmitis after IVI has a higher likelihood of being due to oral flora compared with endophthalmitis after PPV. Among IVI patients, worse visual outcomes occurred when endophthalmitis was due to oral flora. Abstract : Endophthalmitis after intravitreal injection has a higher likelihood of being due to oral flora compared with endophthalmitis after pars plana vitrectomy. Among intravitreal injection patients, worse visual outcomes occurred when endophthalmitis was due to oral flora.